PEMBELAJARAN ANSAMBEL GESEK EKSTRAKURIKULER DI SMK METHODIST CHARLES WESLEY MEDAN - Simanjuntak, Kevin Justinus Elwadi (Universitas Negeri Medan, 2018)
This study is about the String Ensemble Learning in Extracurricular at SMK MethodistCharles Wesley Medan. The purpose of learning is to know the learning process of stringensemble extracurricular, knowing in teaching methods and materials string ensemble, knowingthe learning ability of ensembles extracurricular participant, and to identify constraints stringensemble extracurricular teaching at SMK Methodist Charles Wesley Medan.The study is based on theoretical foundation to explain the theory of learning, thelearning component, understanding ability, sense of ensemble, string ensemble understanding, andextracurricular activities.This study will take a place in Jalan Padang Golf (In), Central Business District BlockCC-DD Polonia, Medan Polonia. This study uses descriptive qualitative research, observation,interviews, documentation and literature review. The samples are part of the population that isabout to be investigated, which in this study were teachers and all students who take the stringensemble extracurricular activities are 15 students and 1 teacher.Once the entire data has been collected, then analyzed to answer all the questions ofthe study. The learning process is carried out for 60 minutes, the time used to explain the theory isa 15-minute and 45-minute practice. The implementation stage string ensemble learning studentswho take these activities are all students in both the junior high school students Methodist CharlesWesley, the high school students of Charles Wesley Methodist School, and SMK Methodist CharlesWesley were merged into a single string ensemble group.In the ensemble learning process swipe at SMK Methodist Charles Wesley Medanmaterial used is a script of classical music such as Baroque and Rokoko, Romantic, Classical andContemporary Classical. The obstacles in the form of incomplete facilities, differences in levels ofstudent proficiency, and student attendance in a regular schedule that already exists. Students canbe said to be capable of if the students can play an instrument properly, in accordance with goodtechnique, mastering the material well, and can play with a harmonious ensemble.